2021
DOI: 10.3389/fphar.2021.653525
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A5 and UGT1A9 Polymorphisms Influence Immunosuppressive Therapy in Pediatric Kidney Transplant Recipients

Abstract: Background: Tacrolimus (TAC) and mycophenolic acid (MPA) are the main immunosuppressive drugs used in pediatric kidney transplantation. Single nucleotide polymorphisms (SNPs) in metabolizing enzymes and transporters might influence plasma levels of these drugs. Herein, we sought to determine the influence of SNPs on CYP3A5, MRP2 and UGT1A9 genes in Chilean pediatric kidney recipients using TAC and MPA.Patients and Methods: A prospective study was performed on 104 pediatric kidney recipients that used TAC and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
2
7
0
2
Order By: Relevance
“…Moreover, a Chilean study showed that carriers of the UGT1A9-275A allele had lower AUC 0 –12h/MPA-D when compared with UGT1A9-275T carriers. Instead, MRP2 and UGT1A9 genotypes did not show significant differences in MPA C 0 , MPA-D, or MPA C 0 /D in 104 pediatric renal transplant recipients [ 76 ]. These results were confirmed by Mazidi et al [ 77 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a Chilean study showed that carriers of the UGT1A9-275A allele had lower AUC 0 –12h/MPA-D when compared with UGT1A9-275T carriers. Instead, MRP2 and UGT1A9 genotypes did not show significant differences in MPA C 0 , MPA-D, or MPA C 0 /D in 104 pediatric renal transplant recipients [ 76 ]. These results were confirmed by Mazidi et al [ 77 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Se ha propuesto que la combinación de los polimorfismos en las isoformas UGT1A9, UGT2B7 y MRP2 (ABCC2) pueden ser importantes predictores de variabilidad interindividual del MPA en población pediátrica 22,23 . Resultados en pacientes pediátricos atendidos en nuestro centro, han mostrado que los portadores del alelo variante UGT1A9-275A tenían un ABC 0-12h /dosis MPA más bajo que los pacientes portadores solo del genotipo del alelo ancestral UGT1A9-275T con una diferencia de significación estadística marginal (p = 0,05) 24 . Estos resultados sugieren que los pacientes portadores de aquel polimorfismo, podrían registrar niveles de C0 y ABC de MPA más bajos que los esperados y por consiguiente requerir mayor dosificación a la estandarizadas por superficie corporal.…”
Section: Discussionunclassified
“…MPA TDM is recommended in pediatric patients, but it is still not a routine practice although numerous studies proved the advantage of dose adjustment based on TDM [66][67][68][69][70][71][72][73]. Our review includes studies on the MPA TDM in children after renal transplantation [67,[74][75][76][77][78][79][80][81], other organ transplantation such as heart [82,83], liver [72], or intestine [65], children after hematopoietic stem cell transplantation [84][85][86][87][88][89] or cord blood transplantation [90], and children with lupus [71,73,[91][92][93][94][95][96], nephrotic syndrome [69,70,[97][98][99][100][101][102][103][104][105]…”
Section: Mpa Characteristicsmentioning
confidence: 99%
“…There has been a discussion on the pharmacogenetic approach to MPA TDM. A recent study conducted by Krall et al [74] showed that CYP3A5 and UGT1A9 genotyping in pediatric recipients might be useful and advisable to guide the dosing and monitoring of MPA and Tac in children that undergo kidney transplantation. Although no significant differences between MRP2 and UGT1A9 genotypes were observed regarding most MPA pharmacokinetic parameters (C 0 , dose, dose-normalized C 0 ), patients carrying the UGT1A9-275A allele had lower dose-normalized AUC 0-12 than those carrying the UGT1A9-275T ancestral allele.…”
Section: Tdm Based On Pharmacogeneticsmentioning
confidence: 99%
See 1 more Smart Citation